2013
DOI: 10.1145/2514641.2514645
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach for optimized bypass configurations for application-specific embedded processors

Abstract: The diversity of today's mobile applications requires embedded processor cores with a high resource efficiency, that means, the devices should provide a high performance at low area requirements and power consumption. The fine-grained parallelism supported by multiple functional units of VLIW architectures offers a high throughput at reasonable low clock frequencies compared to single-core RISC processors. To efficiently utilize the processor pipeline, common system architectures have to cope with data hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Intermediate results from the last three pipeline stages are forwarded to the RD stage (data bypass) and DC stage (control bypass, condition register only). In [9] we have shown that the number of bypass paths heavily grows with the number of implemented VLIW slots and that many of those paths are rarely used while processing certain applications. Due to this, each single bypass path can be implemented or replaced by a stalling mechanism.…”
Section: A the Processor Pipelinementioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate results from the last three pipeline stages are forwarded to the RD stage (data bypass) and DC stage (control bypass, condition register only). In [9] we have shown that the number of bypass paths heavily grows with the number of implemented VLIW slots and that many of those paths are rarely used while processing certain applications. Due to this, each single bypass path can be implemented or replaced by a stalling mechanism.…”
Section: A the Processor Pipelinementioning
confidence: 99%
“…The width of the instruction memory is set to 128 bit. The EX-DC control bypass is disabled as proposed in our previous work [9]. The processor includes 32 general purpose registers, a trace unit, a bus interface, and a UART unit.…”
Section: D E S I G N S P a C E E X P L O R A T I O N O F T H E Cmentioning
confidence: 99%
See 1 more Smart Citation